Diagnosis and management of nasal obstruction in the athlete. A narrative review by subgroup B of the IOC Consensus Group on "Acute Respiratory Illness in the Athlete" - McIntosh, C.; Clemm, H. H.; Sewry, N.; Hrubos-Strøm, H.; Schwellnus, M. (The Journal of Sports Medicine and Physical Fitness, 2021)
Protection of the health of the athlete is required for high level sporting performance. Acute respiratory illness is the leading cause of illness and can compromise training and competition in athletes. To date the focus on respiratory health in athletes has largely been on acute upper respiratory infections and asthma/exercise induced bronchoconstriction (EIB), while nasal conditions have received less attention. The nose has several important physiological functions for the athlete. Nasal conditions causing obstruction to airflow can compromise respiratory health in the athlete, negatively affect quality of life and sleep, cause mouth breathing and ultimately leading to inadequate recovery and reduced exercise performance. Nasal obstruction can be broadly classified as structural (static or dynamic) or mucosal. Mucosal inflammation in the nose (rhinitis) is the most frequent cause of nasal obstruction and is reported to be higher in athletes (21-74%) than in the general population (20-25%). This narrative review provides the sport and exercise medicine physician with a clinical approach to the diagnosis and management of common nasal conditions that can cause nasal obstruction, ultimately leading to improved athlete health and better sports performance.